The double-edged sword effect of algorithmic management on work engagement of platform workers: the roles of appraisals and resources - Feifei Li; Xiaohui Zhan; Yun Liu (Frontiers in Psychology)
PurposeThis study aims to explore how food delivery workers' perceptions of threat and challenge mediate the influence of algorithmic management on their work engagement, and to examine the moderating roles of emotional stability and perceived organizational support (POS) in this process.Design/methodology/approachThe present research conceptualized and validated a framework to investigate the double-edged sword influence of algorithmic management on work engagement, highlighting its potential to be both beneficial and detrimental. Drawing from a sample of 292 delivery workers working in two major food delivery platforms in China, this study employed SPSS 20.0 and MPLUS 7.4 for the statistical examination of the hypotheses.FindingsThe findings reveal that threat appraisal serves as a negative mediator between algorithmic management and work engagement, while challenge appraisal served as a positive mediator in this relationship. Emotional stability and perceived organizational support (POS) acted as moderators of these effects, indicating that when algorithmic management was perceived more as a challenge than a threat, it was more likely to enhance the engagement behavior at work.Practical implicationsThis study uncovers algorithmic management's dual effects. Employees with high emotional stability and organizational support (POS) who view it as a challenge (not threat) show stronger work engagement. Managers should cultivate these psychological resources to enhance technology adoption success.Originality/valueThis study advances the algorithmic management literature by investigating its dual effects on food delivery workers' work engagement. We uncover the underlying mediating mechanisms and demonstrate how emotional stability and perceived organizational support (POS) moderate these relationships.